2016
DOI: 10.1080/09540121.2016.1191604
|View full text |Cite
|
Sign up to set email alerts
|

Childhood victimization and HIV risk behaviors among university students in Saint-Petersburg, Russia

Abstract: Exposure to childhood victimization and abuse has been shown to affect HIV risk in adult populations. In Russia, the existence of child abuse was largely unrecognized until 1990s and its behavioral consequences remain understudied. Our goal was to assess childhood victimization and HIV risk behavior among young adults in Saint-Petersburg, Russia: 743 students from 15 local universities were surveyed. Unprotected sexual intercourse was the most common type of HIV risk behavior: study participants reported no co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 15 publications
1
3
0
7
Order By: Relevance
“…Foram identificados 34 estudos elegíveis, os quais estão resumidamente descritos em https:// doi.org/10.48331/scielodata.YPXI29. Foram publicados entre os anos de 1991 e 2018, em 12 países diferentes (Estados Unidos 8,13-15,18,19,24-40 , Nova Zelândia 7,17,41 , Austrália 9 , Suécia 42 , Filipinas 43 , Canadá 44 , Rússia 45 , China 46 , Costa do Marfim 47 , Zimbábue, Tanzânia e África do Sul 48 ).…”
Section: Descrição Dos Estudosunclassified
See 2 more Smart Citations
“…Foram identificados 34 estudos elegíveis, os quais estão resumidamente descritos em https:// doi.org/10.48331/scielodata.YPXI29. Foram publicados entre os anos de 1991 e 2018, em 12 países diferentes (Estados Unidos 8,13-15,18,19,24-40 , Nova Zelândia 7,17,41 , Austrália 9 , Suécia 42 , Filipinas 43 , Canadá 44 , Rússia 45 , China 46 , Costa do Marfim 47 , Zimbábue, Tanzânia e África do Sul 48 ).…”
Section: Descrição Dos Estudosunclassified
“…Os participantes dos estudos foram selecionados entre população geral 7,9,19,26,32,33,41 , escolares ou universitários 30,31,[34][35][36][37][38][44][45][46][47] , e casos registrados em atendimento de proteção infantil 15,[24][25][26] . Doze estudos avaliaram amostras compostas apenas por mulheres 8,17,18,27,28,31,[34][35][36]40,41,44 e três incluíram somente indivíduos do sexo masculino 32,33,39 .…”
Section: Descrição Dos Estudosunclassified
See 1 more Smart Citation
“…[ 11 ] History of CSA was also found to be associated with high-risk sexual behavior among adolescents, of which unprotected sexual intercourse was the most common. [ 12 ] Consequences of CSA are summarized in Table 1 . [ 13 14 ]…”
mentioning
confidence: 99%
“…There was a positive relationship between the risk of disorder and extent of CSA, with the highest risk of disorder in those had suffered forcible intercourse during abuse. [ 12 ] A systematic review and meta-analysis of 37 longitudinal, epidemiological studies with 3,162,318 participants found a significant association between sexual abuse and anxiety disorder, depression, eating disorders, PTSD, sleep disorders, and suicidal attempts but not with schizophrenia or somatoform disorders. [ 17 ]…”
mentioning
confidence: 99%